HUBUNGAN KEHAMILAN PADA REMAJA DENGAN KEJADIAN BERAT BADAN LAHIR RENDAH PUSKESMAS WORI - Tatontos, Adeleid; Veronika WidiaTrilupi, Raden Maria (NURSING UPDATE : Jurnal Ilmiah Ilmu Keperawatan P-ISSN : 2085-5931 e-ISSN : 2623-2871, 2024)
Background: Adolescent pregnancy is one of the health problems that has a significant impact on both the mother and the baby. One of the risks faced is the occurrence of Low Birth Weight (LBW), which can affect the baby's health in the long term. Adolescents often have less physical and psychological readiness to undergo pregnancy, increasing the risk of complications during pregnancy and childbirth, including LBW. Objective: This study aims to analyze the relationship between adolescent pregnancy and the incidence of LBW at the Wori Health Center. Method: This study used an observational analytical research design with a cross-sectional approach. The sample consisted of 16 adolescent pregnant women who gave birth at the Wori Health Center. Data were collected through medical records and structured interviews, then analyzed using the chi-square statistical test to determine the relationship between adolescent pregnancy variables and the incidence of LBW. Results: The results showed that there was a significant relationship between adolescent pregnancy and the incidence of LBW at the Wori Health Center with a p-value of 0.000 (p <0.05). Most babies born to teenage mothers have a birth weight below 2500 grams, which is categorized as LBW. Conclusion: Pregnancy in teenagers has a significant relationship with an increased risk of LBW. Therefore, it is necessary to carry out education and pregnancy prevention programs for teenagers as well as close monitoring of the health of teenage mothers during pregnancy to reduce the risk of LBW.